ChemInform Abstract: Rational Strategies for the Selective Functionalization of Calixarenes. Issue 39 (September 2015) - Lavendomme, Roy; Zahim, Sara; De Leener, Gael; Inthasot, Alex; Mattiuzzi, Alice; Luhmer, Michel; Reinaud, Olivia; Jabin, Ivan
Abstract Review: [35 refs.